Relative Performances of Central and Dipole Frequency Soundings over a Layered Earth - Patra, H.P.; Nimmagadda, Shastri (Springer Nature, 1982)
Variable frequency soundings in the audio-range replaces shallow conventional direct current methods for determination of layer parameters when surface layer resistivity is high. Central frequency soundings (CFS) is one such method that involves measurement of the existing vertical magnetic field component induced at the centre of a horizontal circular or square loop. Dipole method of frequency sounding using small horizontal coplanar loops (abbreviated DFS) measuring the same field component is also considered. Theoretical studies on CFS and DFS over two- and three-layer horizontally stratified earth are carried out and the response characteristics computed and analysed.